Double-blind Randomized Controlled Trial of Letrozole Versus Clomiphenecitrate in Subfertile Women With Polycystic Ovarian Syndrome. Issue 11 (November 2017) - Amer, S. A.; Smith, J.; Mahran, A.; Fox, P.; Fakis, A.
Abstract : (Abstracted from Hum Reprod 2017;32:1631–1638) For several decades, the standard first-line ovulation induction (OI) agent for women with polycystic ovarian syndrome (PCOS) has been clomiphene citrate (CC). In a number of studies, this agent achieved ovulation rates of approximately 85% and pregnancy rates of 35% to 40%.